Letter from Adele Leopold - Adele Leopold:::::: (1969)
This letter, dated January 27, 1969, from the Democratic State Central Committee of California, invites members of the 1968 California delegation to the Democratic National Convention to attend a breakfast meeting during a statewide issues conference in Los Angeles. The breakfast is scheduled for 8 a.m. on February 8 at the Rodger Young Auditorium, just before the conference's second session. Attendees will receive an off-the-record briefing from Daniel Walker, author of the well-known Walker Report on the Chicago confrontation, and will also discuss California politics with delegation chairman Jess M. Unruh. Recipients are asked to RSVP by February 4. The letter is signed by Adele Leopold, Secretary to the Delegation.